Traditional and emerging ethical concerns in advertising - Lemanski, Jennifer L. (Annales. Etyka w Życiu Gospodarczym, 2019)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PL; mso-bidi-language: AR-SA;">Ethical issues surrounding advertising have been well-discussed. However, over time and alongside societal and media changes, different questions have moved to the forefront in the discussion on advertising ethics. This paper presents an overview of traditional ethical issues of importance in the United States, and analyzes the changes that have come about as a result of newer, more interactive media for ad placements. Although many of the traditional ethical dilemmas remain, the more personalized and interactive nature of new media and an expanded landscape for advertisers to stake their claims have introduced new issues that were previously not of concern, such as privacy.